Study of coal mine modified clean fracturing fluid and optimization of hydraulic fracturing sand adding process - Jun Liu; Jun Liu; Qinghua Zhang; Qinghua Zhang; Chiyu Zhang (Frontiers in Built Environment)
To enhance the permeability of coal seam and improve the gas extraction efficiency is an effective measure to ensure the safety of coal mine production, especially, the research of hydraulic fracturing technology has shown better permeability enhancement efficiency of coal seam. However, when the technology is faced with deep and high stress environment, it is easy to cause“Water lock” in the area near the borehole, thus seriously hindering the efficiency of gas extraction. In order to solve the above problems, we deepened the study of more suitable for the upper hole fracturing resistance, hanging sand, anti-swelling, environmental protection and other requirements of cracking fluid: X3 thickening agent + P1 anti-expansion agent + J3 glue breaking agent, etc., and determined the matching S1 fracturing sand,In Songzao Coal Mine, the gas extraction effect is good after sand fracturing, and the average pure amount of gas extraction is 0.0036 m3/min, which is more than 2 times compared with water fracturing hole. The concentration of gas extraction is up to 65%, and it is 26% on average, which is more than 1 times compared with the concentration of water fracturing hole.The results provide parameter support for improving seam permeability and gas production efficiency, and provide important guidance for mine safety production.